Establishing Grammar Instruction Book Based on Grammar Translation Method to Develop Students Mastery on Grammar: Research and Development - Salim Agus; Supriyono; Sutanti Nita (Universitas Islam Balitar, 2026)
The objective of this research is to develop a grammar instruction book based on the Grammar Translation Method (GTM) to improve students' grammar mastery at the intermediate level. This study addressed the common difficulties faced by Indonesian EFL learners in understanding complex English syntactic structures, such as tenses and passive voice. The methodology employed in this study was Research and Development (R&D) following the five stages of the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. In the analysis phase, it was identified that existing textbooks often lacked clear bilingual explanations, creating a gap in student comprehension. The development phase resulted in a 12-unit instructional guide validated by material and media experts, achieving an average score of 4.5, which falls into the